OCTET‐CY: a phase II study to investigate the efficacy of post‐transplant cyclophosphamide as sole graft‐versus‐host prophylaxis after allogeneic peripheral blood stem cell transplantation. (16th March 2015) - Holtick, Udo; Chemnitz, Jens‐Markus; Shimabukuro‐Vornhagen, Alexander; Theurich, Sebastian; Chakupurakal, Geothy; Krause, Anke; Fiedler, Anne; Luznik, Leo; Hellmich, Martin; Wolf, Dominik; Hallek, Michael; von Bergwelt‐Baildon, Michael; et al.
Abstract: Objective: Post‐transplant cyclophosphamide is increasingly used as graft‐versus‐host disease (GvHD) prophylaxis in the setting of bone marrow transplantation. No data have been published on the use of single‐agent GvHD prophylaxis with post‐transplant cyclophosphamide in the setting of peripheral blood stem cell transplantation (PBSCT). Methods: In a phase II trial, 11 patients with myeloma or lymphoma underwent conditioning with fludarabine and busulfan followed by T‐replete PBSCT and application of 50 mg/kg/d of cyclophosphamide on day+3 and +4 without other concurrent immunosuppression (IS). Results: Median time to leukocyte, neutrophil, and platelet engraftment was 18, 21, and 18 d. The incidence of grade II–IV and grade III–IV GvHD was 45% and 27%, with a non‐relapse mortality (NRM) of 36% at one and 2 yr. After median follow‐up of 927 d, overall and relapse‐free survival was 64% and 34%. Three patients did not require any further systemic IS until day+100 and thereafter. Analysis of immune reconstitution demonstrated rapid T‐ and NK‐cell recovery. B‐ and CD3+/CD161+NK/T‐cell recovery was superior in patients not receiving additional IS. Conclusion: Post‐transplant cyclophosphamide as sole IS in PBSCT is feasible and allows rapid immune recovery. Increased rates of severe acute GvHD explain the observed NRM and may advise a temporary combination partner such as mTor‐inhibitors in the PBSCT setting.